2007
DOI: 10.1152/ajpgi.00341.2006
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilia is induced in the colon of Th2-sensitized mice upon exposure to locally expressed antigen

Abstract: Eosinophilic inflammation is a feature of a variety of gastrointestinal (GI) disorders including eosinophil-associated GI disorder, allergy, inflammatory bowel disease, and parasite infection. Elucidating the mechanisms of eosinophil infiltration into the GI tract is important to the understanding of multiple disease processes. We hypothesize that eosinophilia in the large intestine (colon) can be induced by an antigen in a host that is associated with Th2-skewed antigen-specific immune responses. To investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 85 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…4,21,22 Antigen challenge through the nose of animals pre-sensitized to the same antigen induced eosinophilia in the lung but not in the intestine. 23 As shown in our recent study, 11 oral immunization with nanoparticles that target the large intestinal mucosa did not induce immune responses in the small intestine while immunization targeting the small intestine failed to elicit the large intestinal immune responses as well. These discriminations may result from the differences in specialized anatomical and immunological features of the intestinal wall 24 or the presence of and gut interaction with commensal bacteria in the lumen.…”
Section: Evading Roadblocks In the Gut Lumenmentioning
confidence: 74%
“…4,21,22 Antigen challenge through the nose of animals pre-sensitized to the same antigen induced eosinophilia in the lung but not in the intestine. 23 As shown in our recent study, 11 oral immunization with nanoparticles that target the large intestinal mucosa did not induce immune responses in the small intestine while immunization targeting the small intestine failed to elicit the large intestinal immune responses as well. These discriminations may result from the differences in specialized anatomical and immunological features of the intestinal wall 24 or the presence of and gut interaction with commensal bacteria in the lumen.…”
Section: Evading Roadblocks In the Gut Lumenmentioning
confidence: 74%
“…The Th-2 driven allergic component has been reported as an eosinophilia found in autistic children with gluten sensitivity (Ashwood et al, 2003(Ashwood et al, , 2004. Zhu et al (2007) recently described the role of eosinophil infiltration in the gut of sensitized mice. As reviewed in , pediatric autistic patients maintained on gluten-free diets exhibited a reduced number of eosinophils upon biopsy (Ashwood et al, 2003).…”
Section: Mucosal Immunitymentioning
confidence: 99%
“…Aging significantly affects a number of physiological and biochemical functions that are performed by the liver (Kitani, 1994). Aging has been suggested as a major risk factor for the development of various diseases (Rodwell et al, 2002), and several studies showed that aging increased the risks for numerous liver diseases that cause an increase in the mortality rate (Amarapurkar et al, 2007; Regev & Schiff, 2001; Sheedfar et al, 2013). Previous studies have shown that the liver size progressively decreased in response to aging and a marked decline in volume was found to occur above the age of 60 years in humans (Woodhouse & James, 1990).…”
Section: Introductionmentioning
confidence: 99%